Microearthquakes illuminate the deep structure of the endglacial Pärvie fault, northern Sweden - Lindblom, E.; Lund, B.; Tryggvason, A.; Uski, M.; Bödvarsson, R.; Juhlin, Christopher; Roberts, R. (Oxford University Press, 2015)
© The Author 2015. Published by Oxford University Press on behalf of The Royal Astronomical Society. At 155 km, the Pärvie fault is the world's longest known endglacial fault (EGF). It is located in northernmost Sweden in a region where several kilometre-scale EGFs have been identified. Based on studies of Quaternary deposits, landslides and liquefaction structures, these faults are inferred to have ruptured as large earthquakes when the latest ice sheet disappeared from the region, some 9500 yr ago. The EGFs still exhibit relatively high seismic activity, and here we present new earthquake data from northern Sweden in general and the Pärvie fault in particular. More than 1450 earthquakes have been recorded in Sweden north of 66° latitude in the years 2000-2013. There is a remarkable correlation between this seismicity and the mapped EGF scarps. We find that 71 per cent of the observed earthquakes north of 66° locate within 30 km to the southeast and 10 km to the northwest of the EGFs, which is consistent with the EGFs' observed reverse faulting mechanisms, with dips to the southeast. In order to further investigate the seismicity along the Pärvie fault we installed a temporary seismic network in the area between 2007 and 2010. In addition to the routine automatic detection and location algorithm, we devised a waveform cross-correlation technique which resulted in a 50 per cent increase of the catalogue and a total of 1046 events along the Pärvie fault system between 2003 and 2013. The earthquakes were used to establish an improved velocity model for the area, using 3-D local earthquake tomography. The resulting 3-D velocity model shows smooth, minor velocity variations in the area. All events were relocated in this new 3-D model. A tight cluster on the central part of the Pärvie fault, where the rate of seismicity is the highest, could be relocated with high precision relative location. We performed depth phase analysis on 40 of the larger events to further constrain the hypocentral locations. We find that the seismicity on the Pärvie fault correlates very well with the mapped surface trace of the fault. The events do not align along a well-defined fault plane at depth but form a zone of seismicity that dips between 30° and 60° to the southeast of the surface fault trace, with distinct along-strike variations. The seismic zone extends to approximately 35 km depth. Using this geometry and earthquake scaling relations, we estimate that the endglacial Pärvie earthquake had a magnitude of 8.0 ± 0.4.